PENINGKATAN PEMAHAMAN GEREJA DALAM PENDIDIKAN AGAMA KATOLIK DENGAN GOOGLE CLASSROOM - Werang, Anselmus Sina (Bahasa Indonesia, 2024)
This study focuses on improving the learning outcomes of grade XII students majoring in Social Sciences (IPS) 2 at SMA Negeri 1 Tarakan by utilizing Google Classroom as a learning medium. The methodology used includes observation, implementation of actions, and data archiving involving four students during the research process. The study results showed a significant increase in academic achievement, with a rise of 75% in the first cycle and 100% in the second cycle. However, even though these positive results were achieved, there was a gap in some students who still had not reached the expected level of achievement. Finally, the implications of this study confirm that there is effectiveness through the use of Google Classroom media in supporting distance learning and show the importance for teachers in adopting suitable press to improve the quality of education according to student needs.